Analysis of paracetamol in forensic blowfly samples from intoxicated-paracetamol carcass - Almie Amira Munaras Khan,; Wan Mohd Asyraf Wan Mahmood,; Siti Aisyah Shamsuddin,; Nurul Syahnidz Adila Zaini,; Khairulmazidah Mohamed,; Rumiza Abd Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Paracetamol is one of the most commonly used analgesic drugs that often reported to be abused and involved in intoxication death cases. Some of these cases involved decomposed biological samples from the dead remains, which cannot be analysed appropriately by methods applied for ante mortem specimens. In this study a method for determining paracetamol in entomological samples obtained from decomposed paracetamol-intoxicated carcass is described. As alternative, entomological samples which is blowflies larvae was used for toxicology analysis since immature blowflies were the main processor for the dead remains. To obtain a paracetamol-exposed carcass, New Zealand white rabbits were ingested with 5600 mg/kg (dose) of paracetamol and were let to decompose. Blowflies larvae consumed the carcasses were collected and paracetamol from the larvae were analysed using High Performance Liquid Chromatography with Diode Array Detector (HPLC-DAD). Paracetamol extraction from blowflies’ larvae was done using Solid Phase Extraction (SPE). Separation was conducted under 75:25 ratios of acidified water (pH=3) and acetonitrile, using a C-18 column. Calibration curve was obtained with linear regression (R2) of 0.9999. Paracetamol peak was eluted out at retention time of 3.7 minutes. The entomological specimen from third instar larvae found out to contain the highest concentration of paracetamol.